Prevalence and functional consequences of femoroacetabular impingement in young male ice hockey players - Brunner, R.; Maffiuletti, N. A.; Casartelli, N. C.; Bizzini, M.; Sutter, R.; Pfirrmann, C. W.; Leunig, M. (The American Journal of Sports Medicine, 2016)
Background: Femoroacetabular impingement (FAI), which is highly prevalent in adult ice hockey players, is often associated with negative clinical and functional outcomes. It is unclear, however, whether FAI-related bony deformities and symptoms may lead to functional alterations as reflected in hip muscle strength, range of motion (ROM), and on-ice physical performance in youth ice hockey players.